EXPERIMENTAL STUDIES ON PELLETIZING DIE HOLE CONFIGURATION IN EXTRUDER FOR FISH FORMULA FEED - Igor Alexeyevich Khozyayev; Dmitry Vladimirovich Rudoy (Advanced Engineering Research, 2012)
The effect of the die hole configuration in the screw extruder on the pellet quality of the fish formula feed is considered. The results of the corresponding theoretical and experimental research are presented. The surface form of the die hole that allow to produce uniform pressure of the pressable material throughout the hole length is equated. The curvilinear equation to determine the capacity under the even pressure distribution in the die hole is obtained. The pressure values along the hole length are determined experimentally, and the dependences of the hole capacity and the length on the pressures are developed. Basic requirements to the pellet quality are connected with the fish feeding specificity: durability, water resistance, crumbling, and density of pellets. The hole configuration is evaluated just according to the final quality of the mixed feed. The obtained results prove the advantages of the developed experimental die hole in comparison with the common forms. Firstly, the application of such hole in the extruder increases energy efficiency of the pressing-through process. Secondly, the pellet quality is improved.